Implementation of promotion mix in increasing sales at Janji Jiwa Coffee Volume 841 - Mukti, Artin Bayu; Pertiwi, Ani; Rosyid, Azis Nur (Journal of Gastro Tourism, 2024)
This research aims to identify the application of the promotion mix at Janji Jiwa Coffee Shop Volume 841. This research uses descriptive qualitative research and data source collection with observation and in-depth interview method. The informant is the manager and owner of Janji Jiwa Coffee Shop Volume 841. Findings of this research indicate that Janji Jiwa Coffee Shop Volume 841 applies four promotion mix variables from the five existing variables. (i) Advertising using paid promote, billboards and banners. (ii) Personal selling by fostering good relations by coming directly to the house. (iii) Direct marketing, in collaboration with grabfood and gofood. (iv) Sales promotion with bonus vouchers, free coffee milk vouchers, and shopeepay cashback vouchers.